Research of Design and Control System of Grab Mechanism of On-orbit Assembly Robot - Jiaqi Zhu; Hasiaoqier Han; Peng Yu; Kang Han; Qingwen Wu (Jixie chuandong)
According to the requirement of the key technology research mission of on-orbit assembly space telescope and in order to implement the on-orbit assembly service effectively，the ground verification scheme of the on-orbit assembly robot and sub-mirror assembly sub-system is designed，the end grab mechanism of the assembly robot is designed and analyzed. The scheme of inserting grasp and expanding lock is adopted in the grasp mechanism，and the control system of the assembly robot is also described. After the calculation and analysis，this design can meet the application requirements of the on-orbit assembly space telescope during the ground verification phase.